Inducing q-switching operation at 1-micron all-fiber laser via lutetium oxide film saturable absorber - Abdul Latiff, Anas; Harun, Sulaiman Wadi; Ab Rahman, Mohd Fauzi; Baharom, Mohamad Faizal; Apsari, Retna (Elsevier, 2020)
We demonstrated a rare-earth element of lutetium oxide (Lu2O3) as a passive saturable absorber (SA) for generating Q-switching operation laser at 1-micron region. The laser cavity is all-fiber ring configuration with a single-clad ytterbium-doped fiber as a gain medium. Under dropcasting fabrication method, the Lu2O3 film with a 20 μm thickness has a linear absorption of ∼ 5 dB. A stable pulse train with a typical pattern of repetition rate (26.25 kHz–46.68 kHz) and pulse width (9.36 μs to 4.59 μs) presence along the increment of pump power from 116 mW to 151 mW. At maximum pump power, the single pulse envelope has a pulse energy of 128.8 nJ with 42 dB signal-to-noise ratio (SNR). The maximum output power is 6 mW and the laser consistently has a peak wavelength at 1067.8 nm. Exploring a new alternative material for saturable absorber is one of direction for better pulse all-fiber laser development, especially at 1-micron region wavelength